The Effect of Savings Shuttle Services and Communication Ethics KSPPS. BMT NU East Java on Member Satisfaction(Case Study at BMT NU Lenteng Branch): (Case Study at BMT NU Lenteng Branch) - Khairun Na'em; Maksum Muktie (Al-Musthofa: Journal of Sharia Economics, 2025)
Customer satisfaction represents a personal assessment of how well a product or service meets predetermined expectations. This investigation seeks to analyze the impact of mobile banking collection services and ethical communication practices on member contentment at BMT NU East Java's Lenteng Branch. Employing quantitative methodology, the study engaged 100 carefully selected participants through targeted sampling techniques. Research data was gathered via survey instruments and processed using multivariate regression analysis with SPSS 26. The findings demonstrate that mobile collection services and communication standards positively and substantially affect member satisfaction, both individually and collectively. Subsequent studies might benefit from examining additional influential variables or incorporating qualitative and mixed-method designs, including in-depth interviews, to obtain more comprehensive insights into member perspectives